RESOLUTION OF DISPUTES REGARDING CORPORATE BONDS DECLARED BANKRUPT BY COMMERCIAL COURT - Rafie, Patih Ahmad; Merta, M. Martindo; Junaidi, Junaidi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2024)
The objective of this study is to examine the resolution process for corporate bonds that have been declared bankrupt by the commercial court. This research adopts a normative legal approach, which involves analyzing the law as a comprehensive system comprising legal principles, norms, and rules. The findings of this analysis reveal that the Law of the Republic of Indonesia Number 8 of 1995, which pertains to the capital market, encompasses provisions on bonds. Additionally, article 1 number 3 of the finance ministerial regulation Number 27 of 2020 specifically regulates government securities (SUN) that qualify as bonds. These bonds have a maturity period exceeding one year and are accompanied by coupon payments and limited interest installments (discounts). Bonds can be interpreted as a form of liability protection offered by bond issuers to investors, along with an agreement to repay the principal amount and premium coupons at a predetermined time. Notably, in the case of a company or issuer being declared bankrupt, it is crucial to examine the settlement system for these bonds.